Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Phân tích đa thức thành nhân tử:
\(a^2\)(1+a)-\(b^2\)(1-b)-\(a^2b^2\)(a+b)
Giúp mình với!!
=a^2 + a^3 -b^2 +b^3 -a^2b^2(a+b)
=(a^2-b^2) + (a^3+b^3) -a^2b^2(a+b)
=(a-b)(a+b) + (a+b)(a^2-ab+b^2) - a^2b^2(a+b)
=(a+b)(a-b+a^2-ab+b^2-a^2b^2)
=(a+b) ( (a-ab) -(b-b^2) +a^2(1-b^2) )
=(a+b) ( a(1-b) - b(1-b) + a^2(1-b)(1+b) )
=(a+b) (1-b)(a-b+a^2+a^2b)
=(a+b)(1-b) ( a(1+a) -b(1-a^2) )
=(a+b)(1-b) (a(1+a) -b(1-a)(1+a) )
=(a+b)(1-b)(1+a)(a-b+ab)
=a^2 + a^3 -b^2 +b^3 -a^2b^2(a+b)
=(a^2-b^2) + (a^3+b^3) -a^2b^2(a+b)
=(a-b)(a+b) + (a+b)(a^2-ab+b^2) - a^2b^2(a+b)
=(a+b)(a-b+a^2-ab+b^2-a^2b^2)
=(a+b) ( (a-ab) -(b-b^2) +a^2(1-b^2) )
=(a+b) ( a(1-b) - b(1-b) + a^2(1-b)(1+b) )
=(a+b) (1-b)(a-b+a^2+a^2b)
=(a+b)(1-b) ( a(1+a) -b(1-a^2) )
=(a+b)(1-b) (a(1+a) -b(1-a)(1+a) )
=(a+b)(1-b)(1+a)(a-b+ab)